2018
DOI: 10.1007/s13296-018-0173-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Boundary Conditions on the Behavior of Stiffened and Un-Stiffened Cylindrical Shells

Abstract: The effect of boundary conditions is very important in the analysis of cylindrical shells, and is rarely studied in the literature due to its difficult experimental simulation. For large structures such as shell roofs, the type of boundary supports is among the major factors that can minimize the stresses and deflections. In this study, experimental and numerical investigations of the effect of different boundary supports for stiffened and un-stiffened cylindrical shells were conducted. Two different models of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…The authors reported the maximum deflections and deformed shapes for varying stiffener orientations. Ou et al 24 conducted nonlinear dynamic analysis of composite stiffened cylindrical shells while Temami et al 25 studied the effect of boundary conditions on the behavior of stiffened and un-stiffened isotropic cylindrical shells.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported the maximum deflections and deformed shapes for varying stiffener orientations. Ou et al 24 conducted nonlinear dynamic analysis of composite stiffened cylindrical shells while Temami et al 25 studied the effect of boundary conditions on the behavior of stiffened and un-stiffened isotropic cylindrical shells.…”
Section: Introductionmentioning
confidence: 99%
“…of vibration and sound radiation of double-walled steel cylindrical shells is crucial to guide the structural design and improve the stealth performance. Based on analytical and numerical methods, there is a huge number of works of literature focusing on the dynamic behaviours of cylindrical shells (Mukhopadhyay and Sinha 1992;Ruotolo 2001;Park et al 2016;Rawat et al 2019;Temami et al 2019). Some analytical methods have been presented for the vibration responses of steel shells, which include Wave analysis method (Li 2009;Gan et al 2009), Fourier spectral element method (Jin et al 2017;Su et al 2016) and Transfer matrix method (Irie et al1984;Wang et al 2015).…”
mentioning
confidence: 99%